Hilirisasi kelapa membangun ekosistem berkelanjutan untuk pertumbuhan ekonomi - Arbin, Alfiandi; Mohi, Sarahwati; Tansala, Gabriela Stefany; Haluti, Islamiyati Jahada (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to explore the potential of coconut downstreaming in improving the local economy and creating a sustainable ecosystem. The findings show that coconut downstreaming can increase the added value of products, with export value increasing by 15% in the last five years, thanks to growing global demand. The process of processing coconuts into various products, such as coconut oil, fiber, and processed foods, not only increases farmers' income but also creates new jobs. Recommendations from this study include the need for government support in policy and infrastructure, as well as increased collaboration between farmers, industry, and research institutions with these steps, coconut downstreaming has the potential to become a major pillar in sustainable economic development in Indonesia, while maintaining environmental and social sustainability.